Corporate finance in the euro area – including background material - Francesco Drudi; Annalisa Ferrando; Petra Köhler-Ulbrich; David Marqués Iba\~nez; Philippine Cour-Thimann; Vanessa Baugnet; Elmar Stoess; Thomas Vlassopoulos; Carmen Martínez-Carrascal; Katia Tombois; Peter Mc.Goldrick; Carmelo Salleo; et al. (European Central Bank (ECB), 2007)
This report analyses the financial position of non-financial enterprises in the euro area, in particular the amount of external financing, the choice between debt and equity and the composition and maturity structure of debt. It aims at identifying the main features of the euro area, as well as the peculiarities that depend on the country of origin and the sector of activity. Attention is also devoted to assessing whether a country's institutional eatures are correlated with different financial structures by firms. In light of the particular interest in the access of small and medium-sized enterprises (SMEs) to financing, the report also analyses how financing patterns differ across large, medium-sized and small enterprises. Finally, the report discusses the recent trends observed in the corporate finance landscape of the euro area over the past few years. Although it is still too early to pass final judgement, vast structural changes are underway that could have already influenced in a positive way in the availability of external funds for firms. All in all, a comprehensive understanding of corporate finance in the euro area is important from a monetary policy perspective, given its impact on the transmission mechanism and for productivity and economic growth. Moreover, such an understanding is also relevant from a financial stability perspective. A first assessment is now possible eight years into the third stage of Economic and Monetary Union (EMU), given that sufficient data have been accumulated during this period. This assessment is particularly important as the introduction of the single currency has had significant structural effects on the working of financial markets, increasing their size and liquidity, and fostering cross-border competition. The data available for this report generally cover the period 1995-2005, and the cut-off date for the statistics included is 10 March 2007.
Keywords: 330; Unternehmensfinanzierung; Kapitalstruktur; Eurozone; EU-Staaten